2018
DOI: 10.1177/0047287518764344
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Visitor Experiences: Creating and Testing the Tourism Autobiographical Memory Scale

Abstract: The purpose of this study was to test the validity of the new Tourism Autobiographical Memory Scale (TAMS) that measures visitor experience through personal memory. The TAMS uses the autobiographical memory framework to represent the degree to which a travel experience was impactful to a traveler’s life. Visitors were asked to recall a memory from their visit to a national park and rate the memory of the experience based on its impact and frequency of rehearsal on a 7-point scale. Using exploratory factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 50 publications
(90 reference statements)
2
41
0
Order By: Relevance
“…These four factors (46 items) explain 47% of the variance and are named local residents and culture, selfassurance, disorienting dilemma, and joy. The factor of local residents and culture comprises both process and outcomes, which is congruent with other scales that are capturing stages of change in individuals (Glanz, Rimer, and Viswanath 2008;Krebs et al 2018;Jorgenson et al 2019) and previous scales that are attempting to capture the transformative travel experience (Stone et al 2017). The factor of local residents and culture can be described as regrouping items in which transformative travelers are assessing their abilities to interact with local residents and understand their worldview and culture.…”
Section: Exploratory Factor Analysismentioning
confidence: 64%
“…These four factors (46 items) explain 47% of the variance and are named local residents and culture, selfassurance, disorienting dilemma, and joy. The factor of local residents and culture comprises both process and outcomes, which is congruent with other scales that are capturing stages of change in individuals (Glanz, Rimer, and Viswanath 2008;Krebs et al 2018;Jorgenson et al 2019) and previous scales that are attempting to capture the transformative travel experience (Stone et al 2017). The factor of local residents and culture can be described as regrouping items in which transformative travelers are assessing their abilities to interact with local residents and understand their worldview and culture.…”
Section: Exploratory Factor Analysismentioning
confidence: 64%
“…Accessibility is one of the central properties to understand individuals' ability to mentally access their memory, regarding the ease of memory retrieval (Sutin and Robins 2007) and cognitive rehearsal (i.e., thinking) (Boyacioglu and Akfirat 2015). Within tourism, accessibility has been investigated using sensory cues (J. H. Kim and Jang 2016), a destination's products (Yin, Poon, and Su 2017), and visitor experiences (Jorgenson et al 2019). Furthermore, Jorgenson et al (2019) evaluated how frequently a person has thought about the memory of the trip-related events and found that cognitive rehearsal is a key component of tourism autobiographical memory.…”
Section: Potential Dimensions Of Tourism Memory Characteristicsmentioning
confidence: 99%
“…Recently, the concept of a shared memory economy was proposed by Wood (2020) who claimed that memories are "the most valuable commodity" that the tourism industry can offer. Given the importance of memory, tourism studies have advanced an understanding of tourism experience and its link to memory in the following areas: memorable tourism experiences (J. H. Kim 2010; J. H. Kim, Ritchie, and McCormick 2012;Tung and Ritchie 2011a), tourists' emotional experiences (Rahmani, Gnoth, and Mather 2019), functions of autobiographical memory (H. Kim and Chen 2019), autobiographical memory evocation (Yin, Poon, and Su 2017), tourist sensory memory (Agapito, Pinto, and Mendes 2017;Ballantyne, Packer, and Sutherland 2011;Lv, Li, and McCabe 2020), shared memory (Jepson, Stadler, and Spencer 2019), and tourism autobiographical memory (Jorgenson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past two decades, tourism has been characterised by a major shift from tourism products to tourism experiences (Jorgenson et al , 2019; Park and Santos, 2017), which are actively co-created by tourists (Campos et al , 2018). This shift draws on a wider evolution occurring in the management literature from an approach based on the provision of products to an approach based on the co-creation of customer experiences (Forlani and Pencarelli, 2019).…”
Section: Tourism Experience and Tourism Ecosystems In Light Of The Digital Revolutionmentioning
confidence: 99%